The impact of environmental change on rural livelihoods in Zimbabwe: the case of Hurungwe district ward 13 (2006-2014) - Mudimu, Emmaculate (Midlands State University, 2015)
The research investigated the impact of environmental change on rural livelihoods in Zimbabwe using the case study of Hurungwe Ward 13 using the qualitative research method which was complimented by the quantitative method. Focus Group Discussions, questionnaires and direct observations were used to gather information on how environmental change impacts on the livelihoods of the people in the area under study. Semi-structured interviews were also used to get information from key informants like AREX officials and Environmental Monitors from within the Ward. Both underlying and direct causes of environmental change were clearly articulated in the text. Results from the research revealed that there are serious negative impacts on livelihoods as a result of environmental change since soil degradation and climate change have lowered agricultural yields leading to poverty and food insecurity. Depletion of natural resources like vegetation and gold has also affected income earned from the exploitation of these resources and water pollution has led to health problems in both human beings and livestock. The research established that the situation has been worsened by over-reliance on the deteriorating natural resource base which is due to lack of livelihood diversification. It is important for the government and other relevant stakeholders to employ strategies to improve environmental management and livelihood diversification in order to ensure sustainable livelihoods in the country.